Novel implant surface treatment technology
Through femtosecond laser combined with hydroxyapatite suspension treatment technology, the micro/nano multi-stage composite microgroove structure and hydroxyapatite coating on the surface of the implant were constructed, which solved the problem of poor implant surface treatment in the prior art, and significantly improved the osseous binding ability and soft tissue sealing effect of the implant.
Patent Information
- Application Number
- CN202510262510.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing implant surface treatment technology has problems such as different roughness, irregular microstructure, high risk of pollution, insufficient biological activity, resulting in poor binding ability of the implant to bone tissue and poor soft tissue sealing effect.
The implant was treated with femtosecond laser combined with hydroxyapatite suspension evaporation solvent crystallization method to construct a micro/nano multi-stage composite microgroove structure, and a hydroxyapatite coating was formed to improve the bioactivity and osseous binding ability of the implant surface.
By building a soft tissue sealing structure similar to natural teeth, the soft tissue sealing and osseous binding ability around the implant is improved, the repair and aesthetic effect of the implant is improved, and the osseous binding between the implant and the body is enhanced.
Smart Images

Figure CN119857939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bone implants, in particular to a novel implant surface treatment technology. Background Art
[0002] The long-term and stable biological function of implants depends not only on good bone integration, but also on good peri-implant soft tissue closure.
[0003] The biological inertness of implant materials limits their ability to directly integrate with bone tissue and can lead to serious adverse complications. In recent years, a large number of studies have shown that specific micro-nanotopography of implant surfaces can improve roughness and hydrophilicity, which is conducive to the adhesion and proliferation of BMSCs, and can promote the osteogenic differentiation of BMSCs, thereby promoting bone integration at the implant-body interface. In addition, hydroxyapatite coatings contain mineral components similar to bone tissue and have good biological activity, which can enhance the osteogenic ability of BMSCs.
[0004] In addition, the surface morphology of the implant neck is a key factor affecting the adhesion and differentiation of fibroblasts on the implant surface. Existing implant necks are mostly smooth surfaces, with low adhesion strength of fibroblasts and collagen fibers, and are arranged parallel to the implant or in a ring around the implant. The soft tissue sealing effect formed is far inferior to that of natural teeth, and is more susceptible to mechanical and toxin stimulation, which can easily cause peri-implantitis.
[0005] This technology uses femtosecond laser combined with hydroxyapatite suspension evaporation solvent crystallization to treat implants. By constructing a micro / nano multi-level composite micro-groove structure, the collagen fibers at the neck of the implant can be vertically inserted into the implant surface, forming a soft tissue seal similar to natural teeth. At the same time, the surface micro-groove structure and hydroxyapatite coating promote the adhesion, proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells, effectively improving the bone integration effect of the implant.
[0006] Surface modification is the basis for the long-term and effective function of implants. Traditional implant surface treatment technology has the following shortcomings:
[0007] 1. Sandblasting technology: ① Due to the difference in the size of abrasive particles and the instability of actual operation, there are often problems of uneven roughness and irregular microstructure, which is not conducive to the combination of implants and bone tissue; ② During the sandblasting process, fine sand particles may be embedded into the surface of the implant, causing implant contamination and further affecting its application effect in the body.
[0008] 2. Acid etching technology: ① The acid etching process is difficult to control precisely, has poor repeatability, and is prone to forming a surface with uneven roughness; ② It is difficult to form an ideal surface microstructure, which limits the improvement of biological activity; ③ Improper treatment can easily cause surface corrosion and affect the long-term stability of the implant; ④ The residual etching solution on the surface causes changes in the surface chemical composition, which greatly affects its biocompatibility.
[0009] 3. Anodizing technology: ① The processing efficiency is low, complex and time-consuming, and the resulting surface microstructure is single, which is not conducive to cell adhesion and proliferation; ② The thickness of the formed oxide layer is difficult to control. If it is too thick, it will increase the brittleness of the implant, and if it is too thin, it will not have good bone inductivity; ③ It is not suitable for certain specific implant materials.
[0010] 4. Chemical coating technology: ① The bonding strength with the implant matrix is insufficient, and the coating may peel off during long-term use, causing implant failure; ② The coating material has biocompatibility issues.
[0011] 5. Plasma spraying: The bonding strength between the coating and the substrate is relatively low, and microcracks may exist inside the coating, affecting the long-term stability of the implant.
[0012] Therefore, we propose a new implant surface treatment technology to solve this problem. Summary of the invention
[0013] The purpose of the present invention is to provide a new implant surface treatment technology, which has the advantages of being able to perform femtosecond laser combined with hydroxyapatite suspension evaporation solvent crystallization treatment on the implant surface to improve the soft tissue sealing and bone bonding ability around the implant, improve implant restoration and aesthetic effects, and solve the problems raised in the above-mentioned background technology.
[0014] To achieve the above object, the present invention provides the following technical solution: a new implant surface treatment technology, the method comprising the following steps:
[0015] S1: Select hydroxyapatite powder, mix deionized water and hydroxyapatite powder evenly to prepare a hydroxyapatite suspension with a concentration of 8 mg / ml;
[0016] S2: After sealing the screw hole on the implant, immerse the implant in the suspension for 1 min, and then transfer it to a dryer and dry it at 60°C for 2 min;
[0017] S3: Repeat the operation of step S2 for 3 times to form a uniform calcium-phosphorus coating with a thickness of about 200 to 500 nm on the surface of the implant;
[0018] S4: Femtosecond laser processing: The processing device consists of a femtosecond laser system, a three-axis mobile platform, and a rotating platform. First, the implant is fixed on the rotating platform, which rotates at a speed of 400 mm / s. At the same time, the three-axis platform moves vertically at a uniform speed. AOFEMTO femtosecond laser and corresponding regenerative amplifier are used.
[0019] S5: After adjustment, the output laser parameters are wavelength 1030nm, pulse width 300fs, repetition frequency 100kHz. By changing the laser incident angle, the femtosecond laser is vertically irradiated to the implant surface.
[0020] S6: The laser was processed at a speed of 400 mm / s using different numbers of laser beams in parallel to construct micro-groove surface morphologies of different sizes.
[0021] Preferably, in step S1, a ball milling method is used to prepare nano-hydroxyapatite powder with a particle size of 50 to 100 nm and a Ca / P ratio of 1.67.
[0022] Preferably, in step S1, 0.5 wt% polyacrylic acid dispersant is added when preparing the suspension, the magnetic stirring time is 4 hours, the rotation speed is controlled to 800 rpm, and ultrasonic treatment is performed after stirring, the ultrasonic parameters are controlled to 40 kHz, and the ultrasonic time is 30 minutes.
[0023] Preferably, in step S2, gradient drying is set during drying, firstly, initial baking is performed at 60° C. for 2 min, then infrared radiation curing is adopted, and finally vacuum annealing is performed at 200° C. for 2 h.
[0024] Preferably, in step S3, when the implant is cyclically cured, the weight gain is monitored online by a quartz crystal microbalance to achieve three cycles.
[0025] Preferably, in step S3, after the calcium-phosphorus coating is formed, the morphology is detected by field emission scanning electron microscopy, the surface chemical composition is analyzed by X-ray photoelectron spectroscopy, and the bonding strength is evaluated by nanoindentation testing.
[0026] Preferably, in step S4, the repeatability of the three-axis mobile platform is ±0.5 μm, the radial runout of the air-bearing turntable is <1 μm, and the speed adjustment range is 0 to 1000 rpm.
[0027] Preferably, in step S5, the laser beam adopts a spatial light modulator to realize a Top-hat flat-top beam, the laser adopts a spiral scanning mode, and the pitch adjustment range is 10 to 100 μm.
[0028] Preferably, in step S6, argon protection is used for environmental control during laser processing, the O2 concentration is less than 50 ppm, and real-time plasma monitoring is performed.
[0029] Preferably, in step S6, a femtosecond laser is used to form a hole-shaped micro-nano composite structure on the surface of the implant, and the specific data range is:
[0030] Primary roughness structure: groove diameter 10-50 μm, hole depth 4-10 μm;
[0031] Secondary rough structure: hole diameter: 1-2 μm;
[0032] Tertiary roughness structure: pore diameter: 70-100nm.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention has the advantages of being able to perform femtosecond laser combined with hydroxyapatite suspension evaporation solvent crystallization treatment on the surface of the implant to improve the soft tissue sealing and bone bonding ability around the implant, and improve the implant restoration and aesthetic effect. By proposing a femtosecond laser combined with hydroxyapatite suspension evaporation solvent crystallization method to treat the implant surface, while constructing the micro-nano morphology of the implant surface, the calcium-phosphorus coating is melted to improve the biological activity of the implant surface. The method is accurate and controllable, does not contact the implant surface, and the treatment process is pollution-free. By using this technology to construct a micron-nano multi-level composite structure on the implant surface, not only can the collagen fibers at the neck of the implant be vertically inserted into the implant surface to form a soft tissue seal similar to natural teeth, but also promotes the adhesion, proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells on the implant surface, thereby enhancing the bone bonding between the implant and the body.
[0035] 2. The present invention utilizes a femtosecond laser in combination with a hydroxyapatite suspension evaporation solvent crystallization method to treat an implant. First, a hydroxyapatite suspension is prepared, and then evenly sprayed on the implant surface. After drying, a hydroxyapatite coating is prepared. A laser oscillator is used to generate ultrashort pulses of the femtosecond order, which are then propagated through the air to a focusing device to focus the light beam, and the light beam is precisely targeted and focused to an ultrafine spatial region at the micron level. The sample is fixed on a motorized displacement and rotation platform with three-axis motion for processing. The pulse impacts the sample surface vertically, causing local ablation. By adjusting parameters such as pulse power, scanning speed, frequency, and pulse duration, surface micromorphologies with specific shapes, sizes, and spatial arrangements, such as holes, grooves, and coral island-like structures, can be quickly and accurately constructed and prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the implant groove of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] A novel implant surface treatment technology, the method comprising the following steps:
[0039] S1: Select hydroxyapatite powder, mix deionized water and hydroxyapatite powder evenly to prepare a hydroxyapatite suspension with a concentration of 8 mg / ml;
[0040] In this embodiment, in the above step S1, a ball milling method is used to prepare nano-hydroxyapatite powder with a particle size of 50-100 nm and a Ca / P ratio of 1.67.
[0041] Preferably, in the above step S1, 0.5 wt% polyacrylic acid dispersant is added when preparing the suspension, the magnetic stirring time is 4 hours, the rotation speed is controlled to 800 rpm, and ultrasonic treatment is performed after stirring, the ultrasonic parameters are controlled to 40 kHz, and the ultrasonic time is 30 minutes.
[0042] S2: After sealing the screw hole on the implant, immerse the implant in the suspension for 1 min, and then transfer it to a dryer and dry it at 60°C for 2 min;
[0043] In this embodiment, in the above step S2, gradient drying is set during drying, firstly, initial baking is performed at 60°C for 2 minutes, then infrared radiation curing is adopted, and finally vacuum annealing is performed at 200°C for 2 hours.
[0044] S3: Repeat the operation of step S2 for 3 times to form a uniform calcium-phosphorus coating with a thickness of about 200 to 500 nm on the surface of the implant;
[0045] In this embodiment, in the above step S3, when the implant is cyclically cured, the weight gain is monitored online by a quartz crystal microbalance to achieve three cycles.
[0046] In this embodiment, in the above step S3, after the calcium-phosphorus coating is formed, the morphology is detected by field emission scanning electron microscopy, the surface chemical composition is analyzed by X-ray photoelectron spectroscopy, and the bonding strength is evaluated by nanoindentation testing.
[0047] S4: Femtosecond laser processing: The processing device consists of a femtosecond laser system, a three-axis mobile platform, and a rotating platform. First, the implant is fixed on the rotating platform, which rotates at a speed of 400 mm / s. At the same time, the three-axis platform moves vertically at a uniform speed. AOFEMTO femtosecond laser and corresponding regenerative amplifier are used.
[0048] In this embodiment, in the above step S4, the repeatability of the three-axis mobile platform is ±0.5 μm, the radial runout of the air-bearing turntable is <1 μm, and the speed adjustment range is 0 to 1000 rpm.
[0049] S5: After adjustment, the output laser parameters are wavelength 1030nm, pulse width 300fs, repetition frequency 100kHz. By changing the laser incident angle, the femtosecond laser is vertically irradiated to the implant surface.
[0050] In this embodiment, in the above step S5, the laser beam adopts a spatial light modulator to realize a Top-hat flat-top beam, the laser adopts a spiral scanning mode, and the pitch adjustment range is 10 to 100 μm.
[0051] S6: The laser was processed at a speed of 400 mm / s using different numbers of laser beams in parallel to construct micro-groove surface morphologies of different sizes.
[0052] In this embodiment, in the above step S6, the environment control during laser processing adopts argon protection, the O2 concentration is less than 50ppm, and real-time plasma monitoring is performed.
[0053] In this embodiment, in the above step S6, a femtosecond laser is used to form a hole-shaped micro-nano composite structure on the surface of the implant, and the specific data range is:
[0054] Primary roughness structure: groove diameter 10-50 μm, hole depth 4-10 μm;
[0055] Secondary rough structure: hole diameter: 1-2 μm;
[0056] Tertiary roughness structure: pore diameter: 70-100nm.
[0057] In summary, the present invention utilizes a femtosecond laser in combination with a hydroxyapatite suspension evaporation solvent crystallization method to treat an implant. First, a hydroxyapatite suspension is prepared, and then evenly sprayed on the implant surface. After drying, a hydroxyapatite coating is prepared. A femtosecond ultrashort pulse is generated by a laser oscillator, and the light beam is focused after being propagated through the air to a focusing device, and the light beam is precisely targeted and focused to an ultrafine spatial region at the micron level. The sample is fixed on a motorized displacement and rotation platform with three-axis motion for processing. The pulse impacts the sample surface vertically, causing local ablation. By adjusting parameters such as pulse power, scanning speed, frequency, and pulse duration, surface micromorphologies with specific shapes, sizes, and spatial arrangements, such as holes, grooves, and coral island-like structures, can be quickly and accurately constructed and prepared.
[0058] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A new implant surface treatment technology, characterized in that: The steps include: S1: Select hydroxyapatite powder, mix deionized water and hydroxyapatite powder evenly to prepare a hydroxyapatite suspension with a concentration of 8 mg / ml; S2: After sealing the screw hole on the implant, immerse the implant in the suspension for 1 min, and then transfer it to a dryer and dry it at 60°C for 2 min; S3: Repeat the operation of step S2 for 3 times to form a uniform calcium-phosphorus coating with a thickness of about 200 to 500 nm on the surface of the implant; S4: Femtosecond laser processing: The processing device consists of a femtosecond laser system, a three-axis mobile platform, and a rotating platform. First, the implant is fixed on the rotating platform, which rotates at a speed of 400 mm / s. At the same time, the three-axis platform moves vertically at a uniform speed. AOFEMTO femtosecond laser and corresponding regenerative amplifier are used. S5: After adjustment, the output laser parameters are wavelength 1030nm, pulse width 300fs, repetition frequency 100kHz. By changing the laser incident angle, the femtosecond laser is vertically irradiated to the implant surface. S6: The laser was processed at a speed of 400 mm / s using different numbers of laser beams in parallel to construct micro-groove surface morphologies of different sizes.
2. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S1, a ball milling method is used to prepare nano-hydroxyapatite powder with a particle size of 50 to 100 nm and a Ca / P ratio of 1.
67.
3. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S1, 0.5 wt% polyacrylic acid dispersant is added when preparing the suspension, the magnetic stirring time is 4 hours, the rotation speed is controlled to 800 rpm, and ultrasonic treatment is performed after stirring, the ultrasonic parameters are controlled to 40 kHz, and the ultrasonic time is 30 minutes.
4. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S2, gradient drying is set during drying, firstly, initial baking is performed at 60°C for 2 minutes, then infrared radiation curing is adopted, and finally vacuum annealing is performed at 200°C for 2 hours.
5. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S3, when the implant is cyclically cured, the weight gain is monitored online by a quartz crystal microbalance to achieve three cycles.
6. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S3, after the calcium-phosphorus coating is formed, the morphology is detected by field emission scanning electron microscopy, the surface chemical composition is analyzed by X-ray photoelectron spectroscopy, and the bonding strength is evaluated by nanoindentation testing.
7. The novel implant surface treatment technology according to claim 1, characterized in that: In step S4, the repeatability of the three-axis mobile platform is ±0.5 μm, the radial runout of the air-floating turntable is <1 μm, and the speed adjustment range is 0 to 1000 rpm.
8. The novel implant surface treatment technology according to claim 1, characterized in that: In the step S5, the laser beam adopts a spatial light modulator to realize a Top-hat flat-top beam, the laser adopts a spiral scanning mode, and the pitch adjustment range is 10 to 100 μm.
9. The novel implant surface treatment technology according to claim 1, characterized in that: In step S6, the environment control during laser processing uses argon protection, the O2 concentration is less than 50ppm, and real-time plasma monitoring is performed.
10. The novel implant surface treatment technology according to claim 1, characterized in that: In step S6, a femtosecond laser is used to form a hole-shaped micro-nano composite structure on the surface of the implant, and the specific data range is: Primary roughness structure: groove diameter 10-50 μm, hole depth 4-10 μm; Secondary rough structure: hole diameter: 1-2 μm; Tertiary roughness structure: pore diameter: 70-100nm.
Citation Information
Patent Citations
Application of femtosecond laser in titanium or titanium alloy implantation material surface treatment
CN101264550A
Dental implant, implant tooth and preparation method of dental implant
CN111728726A
Hydroxyapatite With Controllable Size And Morphology
US20080206554A1
Biomimetic collagen-hydroxyapatite composite material
US20160144071A1
Laser-assisted machining (LAM) of hard tissues and bones
US20160278924A1